Pemanfaatan Eceng Gondok Menjadi Pupuk Organik Cair Di Desa Batujai Kabupaten Lombok Tengah - Rizal Aidi; IGP Muliarta Aryana; I Nyoman Hendri Oka Suardika; Khilda Khairunnisa Fakhruddin (Jurnal Gema Ngabdi, 2021)
Eceng Gondok in Batujai Dam, West Praya District, Central Lombok Regency is a serious problem for the government because of its rapid growth and can damage air sedimentation. The purpose of this activity is to provide counseling and training on the use of Eceng Gondok to become liquid organic fertilizer for the community in Batujai Village. The counseling and training activities were attended by 19 hamlet heads, community leaders, and village youth. This service activity is carried out in several stages, namely surveys, holding counseling as a form of learning assistance, training, and evaluation. This activity was carried out from April to July 2021. Counseling and training on the manufacture of liquid organic fertilizer with Eceng Gondok as raw material was carried out in the Batujai Village Office Hall. The results showed that the participants felt very helpful with the outreach activities regarding the importance of Eceng Gondok to be used as liquid organic fertilizer. Participants have more insight and skills in the Training of Making Organic Liquid Fertilizer (OLF). The resulting Liquid Organic Fertilizer product is applied to plants with an unquestionable level of testing and a Ph that is safe for plants. The introduction of this OLF product is a solution for the Batujai Village community to participate in the use of water hyacinth which is a weed as a government participation program in the form of Zero Waste.